Their life stories are so different and yet so similar. Comparative biographical story of two women-artists (photographer and painter) from the former Czechoslovakia (Theatrum historiae, 2014)
Comparing two life stories (one woman-photographer, one woman-painter), the author handles the topic of limits and possibilities of art production in Czechoslovakia/Czech Republic as they were experienced before and after year 1989. There are discussed issues of institutional restrictions, (self)censorship in the past and market environment today. The comparison includes also women’s personal fates because family backgrounds, families’ attitudes towards the ruling regime as well as motherhood fundamentally affected their career.
Keywords: Czechoslovakia; fine arts; medal-making; painting; photographing; oral history; women-artists